Information on the Space. Systems Transdisciplinary Aspect - Mokiy, V. S. (European Scientific Journal, ESJ, 2020)
The systems transdisciplinary model of spatial unit of order occupies a Central place among other models of the systems transdisciplinary approach. This model demonstrates the structure of potency of objects, which gives it the ability to expediently manifest and transform. This circumstance inextricably connects space, information and time. To prove this connection, the article uses two models of a spatial unit of the order. This is an analogue of the static and dynamic systems transdisciplinary model of spatial unit of order. On the example of the first model, the grounds for the appropriate manifestation of potency are described. On the example of the second model, the grounds for an appropriate transformation of potency are described. The author illustrates the practical possibilities of these models by the example of solving fundamental problems of Microbiology, chemistry, astrophysics, and political geography. The examples given in the article show that the basis of sustainable development of modern society can be based on the natural mechanism of self-organization of an object and functional ensembles of objects. This conclusion formed the basis of technologies for managing the state of natural, man-made and social objects, as well as methods for analyzing the risk of their complex interaction.